Phylogenetic relationships of termitomyces aurantiacus inferred from internal transcribed spacers DNA sequences - Shafiquzzaman Siddiquee; Kobun Rovina; Laila Naher; Kenneth F. Rodrigues; Md Akhter Uzzaman (2010)
Fungus-growing termites cultivate species of the mutualistic basidiomycete genus Termitomyces on a substrate called the fungal comb. Identification of fungal species based on morphological features is complicated, tedious, and prone to errors. As an alternative, nuclear ribosomal DNA sequences consisting of the internal transcribed spacers (ITS1 and ITS2) and 5.8S rDNA were used to identify Malaysian isolates of Termitomyces sp. The morphological characteristics and molecular data indicate that Malaysian Termitomyces isolated is clearly monophyletic and belongs to the Tricholomataceae family. The Malaysian isolates analyzed in this study represent the termite fungus species called T. aurantiacus.